(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
This article grass eraser robots of technology development , application and advantages analysis does In the article , it is important aspects as , of robots work principle , different different sensors and automatic systems using the fires to determine and on shutdown efficiency seeing will be released . Also grass eraser of robots the world across fire safety in the field place , their a person his life in storage role and to nature effect also thought about is conducted . Economical and ecological aspects are also considered is taken , this while robots in the future more wider apply opportunities shows . Article , vol eraser of robots the future and their technological to innovation effect about conclusion with will be completed